TUC Delegation to the Soviet Union, 1924 (1924)
1924 1918-1939 "TUC Delegation to the Soviet Union, 1924" [T0100.jpg], 1924 The TUC delegation visited Russia, Ukraine the Caucasus and other areas of the Soviet Union between November-December 1924. The delegation met a variety of workers' organisations and, among other activities, interviewed political prisoners, laid a wreath on Lenin's tomb and attended the 6th Congress of All-Russian Trade Unions in the former "Nobles Club" shown here.